The composite operator method route to the 2D Hubbard model and the cuprates - Di Ciolo, A.; Avella, A. (Condensed Matter Physics, 2018)
In this review paper, we illustrate a possible route to obtain a reliable solution of the 2D Hubbard model and
an explanation for some of the unconventional behaviours of underdoped high-Tc cuprate superconductors
within the framework of the composite operator method. The latter is described exhaustively in its fundamental
philosophy, various ingredients and robust machinery to clarify the reasons behind its successful applications
to many diverse strongly correlated systems, controversial phenomenologies and puzzling materials. У цiй оглядовiй статтi ми показуємо можливий шлях до отримання вiрогiдних розв’язкiв для двовимiрної моделi Хаббарда та пояснення деякої незвичної поведiнки недолегованих високотемпературних купратних надпровiдникiв в рамках методу композитних операторiв. Сам метод описано вичерпно в його
фундаментальнiй фiлософiї, рiзних iнгредiєнтах та надiйнiй технiцi для з’ясування причин його успiшного
застосування до рiзноманiтних сильно скорельованих систем, суперечливих феноменологiй та загадкових матерiалiв